ChemInform Abstract: Hypervalent Iodine Induced Oxidative Cross Coupling via Thiophene Cation Radical Intermediate. Issue 18 (11th April 2013) - Dohi, Toshifumi; Ito, Motoki; Sekiguchi, Sho; Ishikado, Yohei; Kita, Yasuyuki
Abstract The presented approach can be combined with known Negishi cross‐coupling for the expeditious access to multiple arylated thiophenes.